Robust control for peg-in-hole assembly - Low, Soon Hing (Nanyang Technological University, 2022)
Peg-in-hole assembly is a form of commonly seen assembly task in the modern world. The assembly process is even more challenging when the clearance of workpiece is very tight. Force feedback controller is a commonly used method to tackle the problem. Depending on the overall contact stiffness, the force controller can be tuned specifically to achieve robust stability. However, the process of tuning controller gains and finding the optimal operating parameters can be very time and resource consuming. A recently proposed controller synthesis framework, CCS has shown its robust stability across multiple contact stiffness with no extra gain tuning. It gave an insight of the possibilities of a single set tuned parameters to perform peg-in-hole assembly in different environments.